Platelet Count, Platelet Indices and some Clotting Parameters among Smokeless Tobacco (Snuff) Consumers in Cross RiverState, Nigeria - Dorathy C. Okpokam Catherine B. Okpara Kooffreh Ada Mbang Stanley O. Anyanwu Joyce E. Etura Chukwuka O. Opara Patience E. Ofem Ogha E. Okpokam Anthony O. Emeribe (Sokoto Journal of Medical Laboratory Science)
No Abstract.